Efecto de la inoculación de hongos micorrízicos arbusculares a plantones de Café (Coffea arabica), variedad Caturra a nivel de vivero en la Región San Martín - Águila Parillo, Karen Marilú Del (2016)
The following research was conducted in Instituto de Investigaciones de la Amazonía Peruana - San Martin (IIAP-SM) Peruvian Amazonia Research Institute. The objective was to determine the effect of the inoculation of arbuscular mycorrhizal fungi to coffee saplings (Coffea arabica L.) variety Caturra, nursery level. The design used was completely randomized (DCA) with 9 treatments (inoculated with HMA-N), and a control treatment (without HMA-N), with significance level α = 0.05, error probability to determine the nature of the differences between treatments. In the study, the inoculation was performed with HMA-N in solid substrate, before they were subjected in a period of multiplication for 60 days in maize (Zea mays). To obtain our results, the variables were: HMA-N multiplication, percentage of colonization, length of extraradicular mycelium, plant height, leaf area, aerial dry biomass and root dry biomass. Next, a correlation analysis was performed. The results of this study showed that the most efficient consortiums were those belonging to the T9, T5 and T8 treatments. This significantly favored the growth and development of coffee plants in the nursery stage